Impact of Online Gambling on Domestic Violence from the Perspective of Islamic Criminal Law - Nadha, Amina Qotrotun; Syafaq, Hammis (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2025)
The phenomenon of online gambling is increasing in Indonesia and has a serious impact on household stability, one of which is domestic violence (KDRT). This study aims to analyze the criminal acts of online gambling that cause domestic violence from the perspective of Islamic criminal law. This research employs a normative conceptual approach. Data is collected through literary studies, specifically by gathering information from laws and regulations, books, and journal articles. The results of the survey show that online gambling can cause economic dysfunction and emotional stress in the family, which has a direct impact on increasing domestic conflicts, even physical and psychological violence. From the perspective of Islamic criminal law, the practice of gambling is jarīmah māliyah that damages the family maintenance structure, while domestic violence is classified as jarīmah nafsiyyah. The treatment of the perpetrator can be through the sanction of ta‘zīr, and in the case of physical injury, diyah can be used as a form of compensation and recovery of the victim. This research offers an integrative approach between sharia norms and social policies in responding to domestic violence due to online gambling, as well as encouraging synergy between the state, society, and religious institutions in family protection.